EVALUATING REGIONAL ABSORPTIVE CAPACITY IN THE IMPLEMENTATION OF SUPER PRIORITY TOURISM DESTINATION (DPSP) POLICY - Ivan Ramadhan; Raniasa Putra; Djunaidi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Abstract This study evaluates the absorptive capacity of local governments in responding to the Super Priority Tourism Destinations (DPSP) policy in Indonesia. While the central government has massively intervened through infrastructure investment and institutional engineering, the realization of tourism economic growth remains hampered by local bottlenecks. Utilizing a qualitative descriptive approach through systematic literature and document review, this research analyzes the implementation of DPSP across five targeted regions using the Realistic Evaluation framework and the Policy Capacity theory. The analysis reveals that the top-down mechanism fails to operate optimally due to the deficit in local policy capacity. Analytically, local governments face delays in synchronizing spatial planning and derivative regulations. Operationally, local fiscal constraints result in inadequate secondary infrastructure and basic utilities. Politically, sectoral ego and jurisdictional conflicts between local leaders and the Tourism Authority Board hinder the realization of collaborative governance, alienating local community participation. The study concludes that infrastructure-driven tourism development must be preceded by capacity-driven interventions. It is highly recommended that the central government establish an asymmetrical funding scheme and systematic capacity-building programs to strengthen the analytical, operational, and political capacities of local bureaucracies.